Discover the answers you need at Westonci.ca, a dynamic Q&A platform where knowledge is shared freely by a community of experts. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts.
Sagot :
Let's solve the equation [tex]\(x - 12 \sqrt{x} + 36 = 0\)[/tex] step by step to find the value of [tex]\(x\)[/tex].
1. Start by setting the equation equal to zero:
[tex]\[ x - 12 \sqrt{x} + 36 = 0 \][/tex]
2. To simplify, let's make a substitution. Let [tex]\( y = \sqrt{x} \)[/tex]. Therefore, [tex]\( y^2 = x \)[/tex].
3. Substituting [tex]\( y \)[/tex] into the equation, we get:
[tex]\[ y^2 - 12y + 36 = 0 \][/tex]
4. This is a quadratic equation in [tex]\( y \)[/tex]. We can solve it using the quadratic formula [tex]\( y = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \)[/tex], where [tex]\( a = 1 \)[/tex], [tex]\( b = -12 \)[/tex], and [tex]\( c = 36 \)[/tex].
5. Let's apply the quadratic formula:
[tex]\[ y = \frac{-(-12) \pm \sqrt{(-12)^2 - 4 \cdot 1 \cdot 36}}{2 \cdot 1} \][/tex]
Simplify inside the square root:
[tex]\[ y = \frac{12 \pm \sqrt{144 - 144}}{2} \][/tex]
[tex]\[ y = \frac{12 \pm \sqrt{0}}{2} \][/tex]
[tex]\[ y = \frac{12 \pm 0}{2} \][/tex]
[tex]\[ y = \frac{12}{2} \][/tex]
[tex]\[ y = 6 \][/tex]
6. Recall that [tex]\( y = \sqrt{x} \)[/tex]. Substituting back, we have:
[tex]\[ \sqrt{x} = 6 \][/tex]
7. Square both sides to solve for [tex]\( x \)[/tex]:
[tex]\[ x = 6^2 \][/tex]
[tex]\[ x = 36 \][/tex]
So, the value of [tex]\( x \)[/tex] is [tex]\( 36 \)[/tex]. Therefore, the correct answer is:
[tex]\[ \boxed{6^2} \][/tex]
1. Start by setting the equation equal to zero:
[tex]\[ x - 12 \sqrt{x} + 36 = 0 \][/tex]
2. To simplify, let's make a substitution. Let [tex]\( y = \sqrt{x} \)[/tex]. Therefore, [tex]\( y^2 = x \)[/tex].
3. Substituting [tex]\( y \)[/tex] into the equation, we get:
[tex]\[ y^2 - 12y + 36 = 0 \][/tex]
4. This is a quadratic equation in [tex]\( y \)[/tex]. We can solve it using the quadratic formula [tex]\( y = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \)[/tex], where [tex]\( a = 1 \)[/tex], [tex]\( b = -12 \)[/tex], and [tex]\( c = 36 \)[/tex].
5. Let's apply the quadratic formula:
[tex]\[ y = \frac{-(-12) \pm \sqrt{(-12)^2 - 4 \cdot 1 \cdot 36}}{2 \cdot 1} \][/tex]
Simplify inside the square root:
[tex]\[ y = \frac{12 \pm \sqrt{144 - 144}}{2} \][/tex]
[tex]\[ y = \frac{12 \pm \sqrt{0}}{2} \][/tex]
[tex]\[ y = \frac{12 \pm 0}{2} \][/tex]
[tex]\[ y = \frac{12}{2} \][/tex]
[tex]\[ y = 6 \][/tex]
6. Recall that [tex]\( y = \sqrt{x} \)[/tex]. Substituting back, we have:
[tex]\[ \sqrt{x} = 6 \][/tex]
7. Square both sides to solve for [tex]\( x \)[/tex]:
[tex]\[ x = 6^2 \][/tex]
[tex]\[ x = 36 \][/tex]
So, the value of [tex]\( x \)[/tex] is [tex]\( 36 \)[/tex]. Therefore, the correct answer is:
[tex]\[ \boxed{6^2} \][/tex]
We hope this was helpful. Please come back whenever you need more information or answers to your queries. We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. Thank you for choosing Westonci.ca as your information source. We look forward to your next visit.